Interaction of the Central Nervous System with the Peripheral System through Cranial Nerves - Bozorboev Shokhrukh (Journal of Science in Medicine and Life, 2025)
Cranial nerves are integral to the central part of the human nervous system, with their complex structures and diverse functions supporting physiological processes and cognitive activities. Primarily, they establish communication between the brain and the body, transmitting motor and sensory signals and regulating various systemic functions. Due to their role in maintaining and restoring human health, cranial nerves are a crucial subject of study not only in medicine but also in other scientific fields. This article provides a detailed analysis of the structure and primary functions of cranial nerves, as well as the importance of their research and future prospects. Through this analysis, a deeper understanding of the intricate mechanisms of the nervous system and their association with various diseases can be achieved.